UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF SISWA KELAS VIII SMP NEGERI 5 PEKANBARU - Syafrida, Mexi; Syahril, Syahril; Ma?aruf, Zuhdi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to determine the improving of students creativethinking ability by applying the experiential learning model, and to know the differencein students improving creative thingking ability in the class applying the experientiallearning method with the class applying the conventional method in SMP Negeri 5Pekanbaru . The population in this study is 296 students that spread over in eightclasses. The sample was taken by simple random sampling method obtained from 2classes with 75 students as the study samples. The design of this study usesnonequivalent control group design. The Instrument of data collection in this study werewritten questions in the form of multiple choice reasoned with 4 choices as much as 13questions through pretest and posttest arranged according the ability to think fluency,flexible thinking ability, original thinking ability, ability to elaborate, and ability toevaluate. The test results were analyzed using descriptive and inferential analysis. Thisstudy shows that the students creative thinking ability taught with the studentsexperiental learning method are higher than those taught with conventional method (P= 0.003, P < 0:05 or H0 is reject ). After the implementation of experiential learning inthe experimental class obtained an average score 70.83% with the creative categoryand the class with conventional models obtained an average score 58.92% with thecategory of quite creative. The results of this study provide information that theapplication of experiential learning models in SMP Negeri 5 Pekanbaru can improvestudents' creative thinking abilities.Keywords: Experiential Learning model, Creative thinking ability